A low-cost sustainable coating: Improving passive daytime radiative cooling performance using the spectral band complementarity method. (June 2022) - Dong, Yan; Han, Han; Wang, Fuqiang; Zhang, Yingjie; Cheng, Ziming; Shi, Xuhang; Yan, Yuying
Abstract: As a passive cooling method without extra energy expenditure, the passive daytime radiative cooling (PDRC) technology has the potential for wide range of applications. Manufacturing PDRC materials with low-cost and high solar band reflectivity are still facing challenges for their commercialization. In the present study, we used the spectral band complementarity method to realize high reflectivity in the sunlight band and excellent cooling performance of the PDRC coating, with a simple, inexpensive, and scalable preparation process. PDRC coating with a solar reflectance of 97.6% was demonstrated by properly designed BaSO4, CaCO3, and SiO2 particles. During the outdoor test, the average daytime temperature of PDRC coating was 8.3 °C lower than the air temperature in the cavity, and 5.5 °C lower than that of commercial white paints. Under the thermal equilibrium condition, the theoretical radiative cooling power of PDRC coating at nighttime and daytime can reach 119.3 W/m 2 and 94.3 W/m 2, respectively. The assessment results indicate that the PDRC coating has the potential for large-scale commercial production, with a low-cost (approximately 0.5/m 2 ) and simple manufacturing process. This study can provide new ideas for the design and preparation of high-performance low-cost PDRC materials. Highlights: PDRC coating with a variety of mixed particles and broad particle size is prepared. The solar reflectance of the prepared PDRC coating is 97.6%. The average daytime temperature of PDRC coatings is 8.3 °C than that of cavity. The prepared PDRC coating has the potential of large-scale commercial production.